Dynamic characterisation of elastomeric engine mounts of different geometry used in automotive industry: simulation approach - Faris, Waleed Fekry; Saad, Fazidah (Inderscience Publishers, 2010)
Generally, the vehicle engine mounting system consists of an engine as the vibration source and several mounts connected to the vehicle structure. The modern engine mounting systems have been successfully used to isolate the driver and passenger from both noise and vibration generated by the engine. However, there is still a need to improve the performance of engine mounting systems because of the requirements of vibration and noise level isolation for passenger cars and also because of the modern car designs that need lighter bodies and more power-intensive engines. Such a weight reduction and increased power requirements will often have adverse effects on vibratory behaviour that it will increase the vibration and noise level. This study is focusing on the current elastomeric engine mounts of different geometry and will also characterise the dynamic properties of elastomeric engine mount. This will be done by having parametric study of different engine mountings. The analysis of engine mounting rubber components should be accompanied by the vibration analysis of the engine mount system. This research opens up a passage to researchers to study and improve the elastomeric engine mount.